Fundamental operations of the political in Beckett’s Molloy [version 1; peer review: 2 approved] - Paul Stewart (Open Research Europe)
The political novel might be defined in terms of “genre,” or a novel’s overt intervention within a pre-established political field. However, this chapter contends that the process of personal individuation and incorporation within the State (or polis) is the fundamental operation of the political within the novel as a form. In order to sketch out the parallel, and paradoxical, operation of becoming an individual subject at the same time as, and in relation to, incorporation into a wider social state, this chapter examines how Samuel Beckett’s Molloy (1951) plots the resistance of its eponymous protagonist against both benign and coercive attempts to (a) define him as an individual, and (b) to assimilate him into the social body on that basis. Drawing on the works of Aristotle, Agamben, Bersani and Rancière, the chapter focuses on Molloy’s methods of avoidance of becoming a state-recognised and state-sanctioned subject and reads this avoidance as a form of resistance to the established polity. It is argued that Beckett’s non-relational art, of which Molloy is an early example, raises important theoretical issues concerning the interconnectivity of the political and the novel at a fundamental level. If the novel is dependent on just the sort of process that Molloy resists – that is on claims of individuality and relation –, can the novel as a form actively resist the political and resist assimilation and incorporation into a pre-established polis?